Predictive factors of overall and major postoperative complications after partial nephrectomy: Results from a multicenter prospective study (The RECORd 1 project). Issue 4 (April 2017) - Mari, A.; Antonelli, A.; Bertolo, R.; Bianchi, G.; Borghesi, M.; Ficarra, V.; Fiori, C.; Furlan, M.; Giancane, S.; Longo, N.; Mirone, V.; Morgia, G.; et al.
Abstract: Introduction and objectives: To analyze postoperative complications and to assess for significant predictive factors during partial nephrectomy (PN) using a large multicenter dataset. Methods: Patients who underwent PN for clinical T1 renal tumors at 19 urological Italian centers (Registry of Conservative Renal Surgery [RECORd] project) were evaluated between 2009 and 2012. Anthropometric data, comorbidities and perioperative outcomes were analyzed. Complications were divided as intra- and postoperative, medical and surgical, as appropriate. The severity of postoperative complications was graded according to the modified Clavien classification system. Patients who experienced intraoperative complications were excluded from the analyses for the potential confounding effect in the evaluation of predicting factors for postoperative complications. Results: Overall, 979 patients were analyzed: open, laparoscopic and robot-assisted (available since 2011) surgical approaches were used in 522 (56.4%), 286 (30.9%) and 117 (12.6%) cases, respectively. Surgical postoperative complications were reported in 121 (13.1%) cases (32 (3.5%) were Clavien 3), medical were reported in 52 (5.6%) cases (3 (0.3%) were Clavien 3). No Clavien 4 complications were reported. At multivariable analysis, ECOG score ≥1 (OR 1.98; p = 0.002), lower preoperative hemoglobin (OR 0.71; p < 0.0001) and open surgical approach (2.91; p = 0.02) were significant predictive factors of overall surgical postoperative complications, ECOG score ≥1 (OR 1.93; p = 0.04) and surgical approach (p = 0.05) were significant predictive factors of Clavien 3 either surgical or medical postoperative complications. Conclusions: Comorbidities and surgical approach should be considered in preoperative evaluation of patients undergoing PN, as they resulted to play a significant role in the occurrence of postoperative complications.